(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Central Warehousing Corporation was established during 1957 to provide logistics support to the agricultural sector. It is a public Warehouse operator offering logistics services to diverse group of clients. CWC operates 432 Warehouses across the country with a storage capacity of 9.96 million tonnes providing warehousing services. This service includes foodgrain warehouses, industrial warehousing, custom bonded warehouses, container freight stations, inland clearance depots and air cargo complexes.Warehousing activities of CWC include food grain warehouses, industrial warehousing, custom bonded warehouses, container freight stations, inland clearance depots and air cargo complexes.Apart from storage and handling, CWC also offers services in the area of clearing forwarding, handling transportation, procurement distribution, dis-infestation services, fumigation services and other ancillary activities.